Pendampingan Pembelajaran IPAS Menggunakan Model Problem Based Learning Dengan Pola Lesson Study Untuk Meningkatkan Keaktifan Siswa Di SDN 5 Anjani - Cahyani, Ririn Dwi; Yakin, Ilmanul; Septiawati, Jumiati; Hasanah, Ziadatul; Hasanah, Vika Rapiatul (Jurnal Literasi dan Pembelajaran Indonesia, 2025)
In learning, teachers often only deliver material conventionally in class, namely using the lecture method, causing students to be inactive when learning takes place. Using the right method or model is very important to increase student activity. Therefore, this research aims to foster aspects of student activity in learning science and science class IV semester II TP 2024/2025 at SDN 5 Anjani. Improving the quality of learning applies a problem-based learning model with the lesson study model and its implementation is carried out in 3 activities, namely: 1) Plan (planning), Do (implementation and observation), and See (reflection). This research was conducted in two cycles, namely cycle I and cycle II. The research sample was class IV students at SDN 5 Anjani, semester II of the 2024/2025 academic year, with a total of 22 students. The results of this research show an increase in students' activeness in science learning from cycle I to cycle II, namely indicators of activeness in collaborating, activeness in asking questions, activeness in answering, and activeness in discussion. Increased student activity due to the implementation of the Lesson Study-based Problem Based Learning model.